Parental control, Communication and Early Childhood Affection - Arturo Toro, Johana Marcela (2023)
The study sought to understand the manifestations of parental control, communication and affection in the raising of children in the early childhood stage. The method was plated from the qualitative paradigm, with historical hermeneutical approach, ethnographic type. The measurement instruments were the focus group interview guide and the life history guide. The collection techniques were life history and the focus group. The participants were 19 families. The information analyzed from the theoretical perspective of Baumrind (1991) indicated that parental control went from authoritarian to authoritative; Traditionally unidirectional communication became bidirectional and in the manifestations of affection they showed some changes due to the influence of social and political frames of reference. In conclusion, families practice parenting styles different from those experienced in their history.